2019
DOI: 10.1002/ejic.201901202
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Alkali Metal Ion on the Crystal Structure and (Mechano)luminescence of Terbium(III) Tetrakis(β‐diketonates)

Abstract: The novel terbium(III) tetrakis(β‐diketonates) M[TbL4] with different alkali metal counterions (Na, K, Cs) based on functionalized trifluoromethylated β‐diketonate are reported. An efficient approach to alkali metal β‐diketonates ML (M = Na, K, Cs) is proposed, which does not require the alkaline media promoting the destruction of 1,3‐dicarbonyl compounds. The transformation of lithium β‐diketonate LiL into the corresponding alkali metal β‐diketonate ML has been achieved under mild conditions using alkali meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…Precedent for the formation of [Tism Pr i Benz ]Cs by this approach is provided by O’Hara’s method for the synthesis of Cs­[N­(SiMe 3 ) 2 ] via reaction of Li­[N­(SiMe 3 ) 2 ] with CsF . A noteworthy feature of O’Hara’s method is that it eliminates the need to use either elemental cesium or organocesium reagents for the synthesis of amide derivatives. , The favorable metathesis between a lithium complex and CsF derives from the low solubility of LiF and has been employed in other systems. , …”
Section: Resultsmentioning
confidence: 99%
“…Precedent for the formation of [Tism Pr i Benz ]Cs by this approach is provided by O’Hara’s method for the synthesis of Cs­[N­(SiMe 3 ) 2 ] via reaction of Li­[N­(SiMe 3 ) 2 ] with CsF . A noteworthy feature of O’Hara’s method is that it eliminates the need to use either elemental cesium or organocesium reagents for the synthesis of amide derivatives. , The favorable metathesis between a lithium complex and CsF derives from the low solubility of LiF and has been employed in other systems. , …”
Section: Resultsmentioning
confidence: 99%
“…In some works, it was shown that the nature of cationic counterparts strongly influences the crystal structure and packing of the complexes as well as their physical properties. [35][36][37] In this work, we report the synthesis, structural characteristics, thermal, and luminescence properties of new dimethyl-Nbenzoylamidophosphate (HL) based lanthanide tetrakis-complexes NEt 4 [LnL 4 ] (Ln 3 + = La, Nd, Sm, Eu, Gd, Tb, Dy) (Scheme 1). Dimethyl-N-benzoylamidophosphate was shown to be a good lanthanide luminescence sensitizer [17,38] and a versatile ligand, which can bind metal ions in different modes.…”
Section: Introductionmentioning
confidence: 99%
“…In their structure, a lanthanide ion is surrounded by four ligands forming a LnO 8 environment and the cationic counterparts are typically alkali metal ions or positively charged N, P‐organic cations. In some works, it was shown that the nature of cationic counterparts strongly influences the crystal structure and packing of the complexes as well as their physical properties [35–37] …”
Section: Introductionmentioning
confidence: 99%
“…Finally, the Cambridge Structural database (CSD, v 5.41, update 2 May 2020) [38] was used to retrieve similar potassium complexes; just one structure was found containing a related CF 3 -β-diketonate ligand (L in the following). [39] Also in the case of the KL complex (CSD Refcode = COYPUE) a 1D polymer is formed. The K••••K distances observed in 1, 2 and 4 are comparable with those published for COYPUE (K••••K distances range = 3.552-4.246 Å).…”
Section: Introductionmentioning
confidence: 99%